2019
DOI: 10.3390/ma12182881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Content on Friction and Wear Properties of Copper Matrix Composites at High Speed Current-Carrying

Abstract: The copper matrix composites were prepared by spark plasma sintering (SPS). The current-carrying friction and wear tests were carried out on a self-made HST-100 high-speed current-carrying friction and wear tester, and the effect of the graphite content on the current-carrying friction and wear properties of the composite material was studied. The results show that with an increase in graphite content, the average friction coefficient and wear rate of the two materials decreased significantly, the fluctuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
(19 reference statements)
0
10
1
Order By: Relevance
“…In previous work of sliding current-carrying contact, the friction coefficient and the conductivity often worsen concurrently and had a strong coupling relationship. 26,27) However, in present results, the real-time current showed obvious pulse fluctuation while the friction coefficient still remained stable (Fig. 3 and Fig.…”
Section: The Failure Life Of Rolling Current-carrying Cu Pairscontrasting
confidence: 51%
“…In previous work of sliding current-carrying contact, the friction coefficient and the conductivity often worsen concurrently and had a strong coupling relationship. 26,27) However, in present results, the real-time current showed obvious pulse fluctuation while the friction coefficient still remained stable (Fig. 3 and Fig.…”
Section: The Failure Life Of Rolling Current-carrying Cu Pairscontrasting
confidence: 51%
“…C and O elements at a higher level indicate oxidation on the sample, which might occur from the thermal oxidation of organic and inorganic ingredients as graphite and MoS2. In previous studies, graphite decomposed into the gas at elevated temperature [35]. Whereas, MoS2 reacted with oxygen and transformed into oxide form (MoO3) at 540 °C [22,43].…”
Section: Morphology Of Worn Surfacementioning
confidence: 93%
“…In the previous studies, the increase in graphite content (0 -10 vol.%) in friction composite significantly reduces wear rates [31]. Yang et al [35] also reported that graphite enhancement (2.5 -10 wt.%) could reduce the average friction coefficient, friction fluctuation, and wear rate.…”
Section: S/n Ratio and Anova For Wearmentioning
confidence: 94%
See 2 more Smart Citations